Do protocells preferentially retain macromolecular solutes upon division/fragmentation? A study based on the extrusion of POPC giant vesicles. Issue 1 (12th December 2017) - Fanti, Alessio; Gammuto, Leandro; Mavelli, Fabio; Stano, Pasquale; Marangoni, Roberto
Abstract : A key process of protocell behaviour is their recursive growth and division, while keeping solutes inside. Abstract : A key process of protocell behaviour is their recursive growth and division. In order to be sustainable, the latter must be characterized by an even and homogeneous partition of the solute molecules initially present in the parent protocell among the daughter ones. Here we have investigated, by means of an artificial division model (extrusion of giant lipid vesicles) and confocal microscopy, the fate of solutes when a large vesicle fragments into many smaller vesicles. Solutes of low- and high-molecular weight such as pyranine, calcein, albumin-FITC, dextran–FITC and carbonic anhydrase have been employed. Although the vesicle extrusion brings about a release of their inner content in the environment, the results shown in this initial report indicate that macromolecules can be partially retained when compared with low-molecular weight ones. Results are discussed from the viewpoint of the life cycle of primitive cells. In particular, the findings suggest that a similar mechanism operating during the critical step of vesicle growth–division could have contributed to primitive evolution.